Stakeholder Analysis in the Implementation of the Agrarian Reform Program in East Lombok Regency - Gibran, Fadel; Pujiriyani, Dwi Wulan; Sugiasih, Sugiasih (Marcapada: Jurnal Kebijakan Pertanahan, 2023)
Stakeholder analysis makes it possible to map the categories of program recipients and organizations implementing agrarian reform programs. Through stakeholder analysis, it is hoped that program acceptance among beneficiary groups can increase. This article aims to examine the implementation of agrarian reform and stakeholder mapping in the case of implementing agrarian reform in Bilok Petung Village. The data for this paper was taken using qualitative methods. Data collection was carried out in two ways: interviews with 12 informants and document studies of journals, books, articles, and related regulations. The data analysis process will be carried out by separating secondary data (literature study) and primary data (field study results). The findings of this research show that there are 11 stakeholders who play an important role in the asset management program and 13 stakeholders who have a main role in the access management program. The findings were then mapped into four quadrants, namely: (1) subject, (2) key players, (3) supporters, and (4) other followers. This research also shows the role of stakeholders in the agrarian reform program, such as policymakers, facilitators, coordinators, planners, implementers, mediators, and accelerators.